ANALYSIS OF FACTORS AFFECTING LABOR ABSORPTION IN INDUSTRIAL SECTORS IN DISTRICT / CITY IN CENTRAL JAVA PROVINCE - Ovy Meilina Tyas Savitri; Sukardi; Heris Kencana TJ (Majalah Imiah Manajemen & Bisnis, 2019)
This research is entitled: "Analysis of Factors Affecting Absorption of Industrial Sector Labor in Districts / Cities in Central Java Province". This study aims to analyze the influence of PMA, PMDN and MSEs on employment in 2014-2017. The analytical method used is panel data regression with Fixed Effect Model. Tests are carried out with a significant level of 5% and processing data using eviews. Based on the results of the regression analysis, it is known that PMA variables have a significant effect on employment, the PMDN variable has a significant effect on employment. While the UMK variable is negative and has no significant effect on employment.